Pengaruh Kualitas Produk, Citra Merk dan Promosi terhadap Keputusan Pembelian Spare part pada Bengkel Aneka Motor Kabupatan Padang Pariaman - Triana Ananda Rustam (Politeknik Ganesha Medan, 2019)
This study aims to determine how much influence the variable quality of the product, brand image and promotions simultaneously and partially on purchasing decisions motorcycle spare parts in the garage Aneka Motor Padang Pariaman. By using the method of data collection in the form of the questionnaire and the analysis method used is multiple linear regression analysis. The result showed that the variable quality of the product, brand image, and promotions significantly influence the purchasing decisions of spare parts in the motor workshop Aneka Motor Padang Pariaman, Marked with the R-value of 0.610 and Adjusted R Square of 0.351. This shows that there is influence between product quality, brand image, and promotions on purchasing decisions by 35.1 % while the remaining 64.9 % is influenced by other variables outside the study. Partial variable product quality and brand image positive and significant influence on purchasing decisions, while the sale does not significantly influence the purchase decision. Keywords : Quality Product, Brand And Promotion Buying Decision